"Sialography and Fistulography of Post-traumatic Fistulae; A Case presentation" - Z. Dalili (Tehran University of Medical Sciences, 2005)
Sialography is the retrograde injection of an iodinated contrast agent into the ductal system of salivary glands and this technique is the only method capable of adequately demonstrating the status of the ductal system. One of the indications of sialography is classification of the salivary ductal system fistulae. This classification has important prognostic and therapeutic values. In the present article, interesting diagnostic findings of combined parotid sialography and extraoral fistulography without using other advanced imaging techniques is discussed in an injured patient.